Biocompatible Peritoneal Dialysis Fluids: Clinical Outcomes - Cho, Yeoungjee (Hindawi Publishing Corporation, 2012)
Peritoneal dialysis (PD) is a preferred home dialysis modality and has a number of added advantages including improved initial patient survival and cost effectiveness over haemodialysis. Despite these benefits, uptake of PD remains relatively low, especially in developed countries. Wider implementation of PD is compromised by higher technique failure from infections (e.g., PD peritonitis) and ultrafiltration failure. These are inevitable consequences of peritoneal injury, which is thought to result primarily from continuous exposure to PD fluids that are characterised by their “unphysiologic” composition. In order to overcome these barriers, a number of more biocompatible PD fluids, with neutral pH, low glucose degradation product content, and bicarbonate buffer have been manufactured over the past two decades. Several preclinical studies have demonstrated their benefit in terms of improvement in host cell defence, peritoneal membrane integrity, and cytokine profile. This paper aims to review randomised controlled trials assessing the use of biocompatible PD fluids and their effect on clinical outcomes.